(untitled) - Malvino, Albert Paul (New York, 1967)
In the book we discuss how to instruments work , what they do and how they are limited. The technician can learn much new material, besides reviewing basic electrical and electronic theory.
Keywords: Electronic instruments,Dụng cụ điện tử